KONSTRUKSI INTERKONEKSITAS ANTAR ILMU ( Tinj a u a n F i ls afat I lm u) - Umam, Munkizul (Jurnal Pelangi Ilmu, 2008)
human funre is really depending on inregrity of the technocrats, scientist, ethics or even the philosophers in Tiain problem_problemhumanity. According to the epistemoTogt that-dissociaiiin of sciince and elllics exactq seen fragile, while froi the aspect of ethial approach, dissociation between sciences and ethics exactly beco;e disasrcr ;f globatl humanity. h is Important to build again tigetherness and aisoiiated sciences for the shake and safety of peopte by analyzing history of sciences qnd vmious dilemma problems in construction of intelconnected sciencd. his dilemma condition at least con be Jinalized ihrough two ways. Firstly, by correlates again the relation of various .science iiscipltnei which for several decades is sepmated as result of classiJicatio, ,\